Comparison of Metal and Plastic Disposable Laryngoscope Blade with Reusable Macintosh Blade in Difficult and Inhalation Injury Airway Scenario: A Manikin Study - Moritz, Andreas; Heinrich, Stefan; Irouschek, Andrea; Birkholz, Torsten; Prottengeier, Johannes; Schmidt, Joachim (Journal of Emergency Medicine, 2017)
Single-use plastic blades (SUPB) and single-use metal blades (SUMB) for direct laryngoscopy and tracheal intubation have not yet been compared with reusable metal blades (RUMB) in difficult airway scenarios.The purpose of our manikin study was to compare the effectiveness of these different laryngoscope blades in a difficult airway scenario, as well as in a difficult airway scenario with simulated severe inhalation injury.Thirty anesthetists performed tracheal intubation (TI) with each of the three laryngoscope blades in the two scenario manikins.In the inhalation injury scenario, SUPB were associated with prolonged intubation times when compared with the metal blades. In the inhalation injury scenario, both metal laryngoscope blades provided a quicker, easier, and safer TI. In the difficult airway scenario, intubation times were significantly prolonged in the SUPB group in comparison to the RUMB group, but there were no significant differences between the SUPB and the SUMB. In this scenario, the RUMB demonstrated the shortest intubation times and seems to be the most effective device.Generally, results are in line with previous studies showing significant disadvantages of SUPB in both manikin scenarios. Therefore, metal blades might be beneficial, especially in the airway management of patients with inhalation injury.
EVALuna2:16733